Results of Investigation of MRSA Susceptibility to Vancomycin in Clinical Units of Large Multifunctional Hospital and Recommendations on Optimization of Antibacterial Therapy of Staphylococcal Infection - V. A. Verikovsky; O. E. Minakov; O. I. Denisova; E. V. Bondarenko (Антибиотики и Химиотерапия)
The frequency of MRSA and MRSE isolates in various units of the Voronezh Regional Hospital was investigated by the results of the local microbiological monitoring for 2014. The maximum position of MRSA was recorded in the ICU (38 to 75% of the strains). The MRSA strains were characterized by higher methicillin resistance, mainly from the cardiosurgical units (60 to 91% of the isolates). The use of the E-test for MRSA susceptibility to vancomycin allowed to estimate the validity of the use of various antibiotics active against MRSA in the treatment of inpatients and to reduce the risk of ineffective therapy.